GIANT MANDIBULAR CYST : A CASE REPORT - Fany Nurul Fawzi Hidayat; Attila Yulaicha Advendila Siregar; Mutiara Aprillia Onasyah Putri; 'Arfa Amali Putri; Betari Ratih Aristyaputri; Rahmadani Widya Atmani; Kintani Arifa Putri; Aris Setyawan (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: The odontogenic keratocyst (OKC) is currently known as a keratocystic odontogenic tumor by the World Health Organization (KCOT). It is described as a benign uni or multicystic intraosseous tumor of odontogenic origin with a distinctive lining of parakeratinized stratified squamous epithelium and the tendency for aggressive, infiltrative activity. This case report features a 54-year-old woman who has an unusual giant mandibular cyst that does not exhibit any of the standard characteristics of developmental odontogenic cysts.case management : the proper treatment in most cases is careful cyst enucleation and removal of the impacted tooth. In view of the large size of the lesion, treatment plan of enucleation was made by taking the cyst capsule in toto and can be treated with decimpressionConclusion: A case of Giant Mandibular Cyst in 54 female treated enucleation and removal of the impacted tooth is presented along with review of literature